Lead Diversification through a Prins-Driven Macrocyclization Strategy: Application to C13-Diversified Bryostatin Analogues - Wender, Paul A.; Billingsley, Kelvin L. (Synthesis, 2013)
The design, synthesis, and biological evaluation of a novel class of C13-diversified bryostatin analogues are described. An innovative and general strategy based on a Prins macrocyclization-nucleophilic trapping cascade was used to achieve late-stage diversification. In vitro analysis of selected library members revealed that modification at the C13 position of the bryostatin scaffold can be used as a diversification handle to regulate biological activity.
Keywords: macrocycles; cyclizations; drugs; polyketides